2008
DOI: 10.1088/0004-6256/135/3/785
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Age-Activity Relation for Cool Stars: The Sloan Digital Sky Survey Data Release 5 Low-Mass Star Spectroscopic Sample

Abstract: We present a spectroscopic analysis of over 38,000 low-mass stars from the Sloan Digital Sky Survey (SDSS) Data Release 5 (DR5). Analysis of this unprecedentedly large sample confirms the previously detected decrease in the fraction of magnetically active stars (as traced by Hα emission) as a function of vertical distance from the Galactic Plane. The magnitude and slope of this effect varies as a function of spectral type. Using simple 1-D dynamical models, we demonstrate that the drop in activity fraction can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
456
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 567 publications
(509 citation statements)
references
References 57 publications
48
456
5
Order By: Relevance
“…Such stars are very active and emit strongly in the near UV, especially when they are young (e.g., West et al, 2008), but the total flux is still less than that of the present-day Sun (Fleming et al, 1993), and the XUV flux (which drives hydrodynamic escape) is not well known. Thus, we expect a range of t des to exist, especially since the orbit evolves with time due to tides, but choose this value for simplicity.…”
Section: The Inner Edge Of the Habitable Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Such stars are very active and emit strongly in the near UV, especially when they are young (e.g., West et al, 2008), but the total flux is still less than that of the present-day Sun (Fleming et al, 1993), and the XUV flux (which drives hydrodynamic escape) is not well known. Thus, we expect a range of t des to exist, especially since the orbit evolves with time due to tides, but choose this value for simplicity.…”
Section: The Inner Edge Of the Habitable Zonementioning
confidence: 99%
“…The stars are very faint and, moreover, prone to flaring. However, there is a secular decrease in activity as the stars age (West et al, 2008), but the data are still too sparse to allow a satisfactory fit. Recent work connected X-ray sources from space telescopes (e.g., GALEX) and ground-based surveys (e.g., Sloan Digital Sky Survey) and found that older low-mass stars tend to emit about 10 -6 to 10 -3 of their energy in the XUV in quiescence (West, personal communication).…”
Section: Fig A2mentioning
confidence: 99%
“…But we only have measurements of radial velocity for two candidates, 2MASS J13570535+3403459 and 2MASS J09332493+3232033, with values of 64.2 and -12.9 km −1 respectively (errors between 5-10 km −1 ) from West et al (2008). They calculated the Galactic space-velocity components (U, V, W ) using photometric distance values of 179 and 180 pc (quite similar to the ones obtained here), obtaining (-32.5, -5.0, 54.0) and (8.4, 1.9, -5.4).…”
Section: Kinematicsmentioning
confidence: 99%
“…The W component is always affected by larger dispersion, so the target may still belong to the young disc area. West et al (2008) calculated vertical distance from the Galactic plane of 146.2 and 188.0 pc that correspond to the thin disc (e.g. Pauli et al 2006).…”
Section: Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation